REVIEW OF THE DEATH PENALTY AGAINST PERPETRATORS OF NARCOTICS CRIME BASED ON SOSIOLOGY OF LAW - Itok Dwi Kurniawan; Vincentius Patria Setyawan (Jurnal Inovasi Penelitian, 2022)
This article describes various public opinions regarding the imposition of the death penalty for drug offenders in Indonesia. The study focused on differences of opinion community in responding to the execution of the death penalty for drug offenders and efforts formulate effective criminal penalties for drug crimes. This article examines it from the point of view of the sociology of law, especially the theory of behaviorism and the theory of justice. In from the perspective of the sociology of law, a sentencing device should include two things, namely: first, it must accommodate the aspirations of the people who demand retaliation as a offset on the basis of the extent of the offender's fault. Second, it must include objectives punishment, namely maintaining and maintaining community unity. With Thus, the law must represent the community's sense of justice. Hence attitudes and actions people who choose the death penalty for drug offenders can justified even though in other places the death penalty is abolished.